Prioritise safety, optimise success! Return to rugby postpartum - Donnelly, G. M.; Coltman, C. E.; Dane, K.; Elliott-Sale, K. J.; Hayman, M.; McCarthy-Ryan, M. F.; Perkins, J.; Rollins, S.; Moore, I. S. (European Journal of Sport Science, 2024)
Pregnancy and childbirth involve substantial physical, physiological and psychological changes. As such, postpartum rugby players should be supported and appropriately prepared to return to the demands of rugby alongside the additional demands of motherhood. This review aims to discuss specific perinatal considerations that inform a rugby player's readiness to return-to-sport postpartum and present an approach to rehabilitation. Before engaging in full rugby training and matchplay, postpartum players should have progressed through the initial phases of rehabilitation and graded sports-specific training to prepare them for the loads they will be exposed to. Additional rehabilitation considerations include minimising deconditioning during pregnancy; medical concerns; the abdominal wall; the pelvic floor; perinatal breast changes, breastfeeding and risk of contact breast injury; body mass; nutritional requirements; hormonal considerations; athlete identity and psychological considerations; joining team training; return to contact and tackle training; evaluating player load tolerance and future research, policy and surveillance needs. A whole-systems, biopsychosocial approach following an evidence informed return-to-sport framework is recommended when rehabilitating postpartum rugby players. Health and exercise professionals are encouraged to use the perinatal-specific recommendations in this review to guide the development of postpartum rehabilitation protocols and resources.